Race and justice: Rodney King and O. J. Simpson in a house divided - Gibbs, Jewelle Taylor (Jossey-Bass Publ., 1996)
Discusses the racial inequality, discrimination, and mistreatment of African-Americans nationwide and particularly of males in Los Angeles, using the cases of Rodney King and O.J. Simpson as examples